ACADEMIC HONESTY IN ACCOUNTING EDUCATION - Hastuti, Maria Eugenia; Alimbudiono, Ria Sandra; Vashti, Isabela Viani (UTSAHA: Journal of Entrepreneurship, 2022)
Academic dishonesty is often found in the educational institution, one of which is in the university. The behavior of academic dishonesty that exists in students, especially accounting students, is an important problem that must be addressed in prevention. As an accounting student who is expected to become an accountant, he should have high integrity toward existing norms and regulations. Therefore, it is necessary to develop the accounting students so that they do not do academic dishonesty that can affect their behavior in the future. In preventing these actions, it is necessary to know the accounting student’s motivation in committing the academic dishonesty. To determine the motivation of academic dishonesty committed by accounting students, the authors applied the method of interviews, observation, and document analysis. The method that implemented are determining the participants’ criteria and making random retrieval data to determine the participant. There are 24 accounting students of 2017 who were taken at one of the universities in Surabaya. The results of the study state that there are different motivations for each student; however, there is one common motivation that is to achieve good grades. From research results that have uncovered the students’ motivations in conducting academic dishonesty, the authors also uncover the effects of academic dishonesty with the ways to prevent it. The ways in preventing the academic dishonesty is by emphasizing self- development in students as an internal means, while external means are by maximizing technological regulations and equipment at the university.